The plastoquinone pool outside the thylakoid membrane serves in plant photoprotection as a reservoir of singlet oxygen scavengers - Ksas, Brigitte; Légeret, Bertrand; Ferretti, Ursula; Chevalier, Anne; Pospíšil, Pavel; Alric, Jean; Havaux, Michel (Plant, cell & environment, 2018)
The Arabidopsis vte1 mutant is devoid of tocopherol and plastochromanol (PC-8). When exposed to excess light energy, vte1 produced more singlet oxygen (1 O2 ) and suffered from extensive oxidative damage compared with the wild type. Here, we show that overexpressing the solanesyl diphosphate synthase 1 (SPS1) gene in vte1 induced a marked accumulation of total plastoquinone (PQ-9) and rendered the vte1 SPS1oex plants tolerant to photooxidative stress, indicating that PQ-9 can replace tocopherol and PC-8 in photoprotection. High total PQ-9 levels were associated with a noticeable decrease in 1 O2 production and higher levels of Hydroxyplastoquinone (PQ-C), a 1 O2 -specific PQ-9 oxidation product. The extra PQ-9 molecules in the vte1 SPS1oex plants were stored in the plastoglobules and the chloroplast envelopes, rather than in the thylakoid membranes, whereas PQ-C was found almost exclusively in the thylakoid membranes. Upon exposure of wild-type plants to high light, the thylakoid PQ-9 pool decreased, whereas the extrathylakoid pool remained unchanged. In vte1 and vte1 SPS1oex plants, the PQ-9 losses in high light were strongly amplified, affecting also the extrathylakoid pool, and PQ-C was found in high amounts in the thylakoids. We conclude that the thylakoid PQ-9 pool acts as a 1 O2 scavenger and is replenished from the extrathylakoid stock.
Keywords: Alkyl and Aryl Transferases; Chlorophyll; Chromatography, High Pressure Liquid; Oxidative Stress; Plastoquinone; alkyltransferasy a aryltransferasy; proteiny huseníčku; chloroplasty; oxidační stres; světlo; tylakoidy; Thylakoids; peroxidace lipidů; singletový kyslík; chlorofyl; plastochinon; Arabidopsis Proteins; scavengery volných radikálů; Light; antioxidant; Free Radical Scavengers; Electron Spin Resonance Spectroscopy; tocopherol; reactive oxygen species; Chloroplasts; Singlet Oxygen; elektronová paramagnetická rezonance; vysokoúčinná kapalinová chromatografie; Lipid Peroxidation